Statins in arterial hypertension treatment - O. N. Tkacheva; N. V. Sharashkina; A. B. Barabashkina; I. M. Novikova; I. E. Mishina (Кардиоваскулярная терапия и профилактика, 1970)
Aim. To analyse cardiovascular risk levels in patients with arterial hypertension (AH); to assess atorvastatin effectiveness in AH patients without cardiovascular events (CVE).Material and methods. In total, 612 CVE-free patients with AH were examined. The participants with SCORE risk level of 5-9% received atorvastatin (10 mg/d) and standard antihypertensive therapy. The authors examined the effects of atorvastatin on blood pressure levels, lipid profile, endothelium-dependent vasodilatation (EDVD) in the brachial artery reactive hyperemia test, intima-media thickness (IMT) of common carotid arteries, C-reactive protein (CRP) concentration, and heart rate variability (HRV).Results. At the end of the study, the atorvastatin group demonstrated a significant decrease in mean levels of total cholesterol (CH), low-density lipoprotein CH and CRP was observed, as well as an increase in EDVD. In addition, in the atorvastatin group, the reduction of sympathetic component of low-frequency and especially very low-frequency HRV was more manifested than in the standard therapy group. In CVE-free patients with AH, atorvastatin therapy (10 mg/d) effectively normalised lipid profile, neuro-humoral and sympatho-adrenal activity parameters, and also demonstrated anti-inflammatory effect.Conclusion. The majority of AH patients have high and very high risk levels and, therefore, require a complex approach towards cardiovascular risk factor modification.